Nursing care provided to young people in two health centers compared with Watson Theory - María Alejandra Pichardo Meza; María Catalina Zúñiga Rodríguez (Universidad de Costa Rica, 2012)
This article has as objective to present the analysis of the care given by the nursing personnel to the young adult population in the Clinic of Pain Control and Palliative Care and in the Onco-hematology Service of the Max Peralta Hospital, related to Jean Watson's theoretical proposal. The study corresponds to a joint research of parallel type with concurrent triangulation. The study populations were made up by twenty-six young adult people (who face morbid process health or chronic pain condition) and four nursing professionals who worked in the Clinic of Pain Control and Palliative Care and in the Onco-hematology Service of the Max Peralta Hospital. A self-executed questionnaire and a semi-structured interview were used to collect the information, which was analyzed using the "SPSS" program and the qualitative categories, respectively. Results: The ten elements of the "Human Care Theory" can be included in the care given by the nursing personnel to the young adult population who faces morbid process health or chronic pain condition. The nursing care mainly focuses on the young adult population quality of life throughout education and pain management. The young adult population perceives a warm, pleasant and human nursing care. Conclusion: Nursing personnel put into practice elements of the Jean Watson's theoretical proposal even when they do not know it.